Comparison by Gas-Liquid Chromatography of the Fatty Acids of Mycobacterium avium and Some Other Nonphotochromogenic Mycobacteria - Thoen, Charles O. (1971)
Fifty-eight strains of nonphotochromogenic mycobacteria representing nine different serotypes were studied, including 38 strains of Mycobacterium avium and 20 strains of Battey bacilli. The lipids were extracted from whole cells, saponified with potassium hydroxide, and esterified with diazomethane. The fatty-acid profiles determined by gas-liquid chromatography included saturated fatty acids ranging from C(8) to C(24), plus some unsaturated analogues and a branched-chain acid. No consistent differences in the fatty-acid profiles were observed between strains of M. avium and Battey bacilli. Quantitative differences in the means (significant at P < 0.01) were observed in the relative amounts of 14:0, 16:1, 18:0, 18:1, and a branched-chain acid among strains of the same serotype. We were unable to differentiate the fatty-acid profiles of recently isolated strains or those maintained in culture for more than 2 years.